PELATIHAN FOTOGRAFI, VIDEOGRAFI DAN MENULIS BERITA DI MEDIA SOSIAL UNTUK PENYANDANG DISABILITAS DI ANNIKA LINDEN CENTRE - I Putu Dudyk Arya Putra; Agung Wijaya (Jurnal Lentera Widya, 2021)
A B S T R A C T English translation. Today's growing digital world also affects the variety of types of work for disabilities. One of the prospective job opportunities for disabled people is freelance work. Freelance work for the disabled is available among others in the world of photography, design and writing such as photographers, news contributors / journalists, graphic design, copywriters, social media admins. These positions certainly require special skills so that disabilities can develop a career in the creative industry sector. If pursued, freelance work can be one of the career alternatives for disability. Many disabled colleagues have an interest in photography but are constrained by physical limitations and the availability of needed devices. Through a series of community service through training in the framework of disability day, want to introduce the world of photography and at the same time utilize the functionality of mobile phones so that it can be maximized by people with disabilities. Photography skills such as editing and other related abilities such as video editing will be useful for disabilities to lead a career into the creative world of photography. The world of photography and journalism are two things that are interrelated, writing becomes a skill mastered by people with disabilities as a writer. The need for journalistic training for disabilities becomes important as a starting point for disability recognizing interests in the field and further building a career in that field. A B S T R A K Dunia digital yang semakin berkembang saat ini turut mempengaruhi variasi jenis pekerjaan bagi disabilitas. Salah satu peluang pekerjaan yang prospektif bagi disabilitas adalah pekerjaan freelance. Pekerjaan freelance bagi disabilitas tersedia antara lain di dunia fotografi, desain dan penulisan contohnya profesi seperti fotografer, kontributor berita/jurnalis, desain grafis, copywriter, admin media sosial. Posisi-posisi tersebut tentunya mensyaratkan keterampilan khusus agar disabilitas dapat mengembangkan karir di sektor industri kreatif tersebut. Apabila ditekuni, pekerjaan freelance dapat menjadi salah satu alternatif karir untuk disabilitas.Banyak rekan disabilitas memiliki minat di dunia fotografi namun terkendala keterbatasan fisik maupun ketersediaan device yang dibutuhkan. Melalui serangkaian pengabdian kepada masyarakat melalui pelatihan dalam rangka hari disabilitas, ingin memperkenalkan dunia fotografi dan sekaligus memanfaatkan fungsionalitas ponsel agar dapat dimaksimalkan oleh penyandang disabilitas. Kemampuan fotografi seperti editing dan kemampuan terkait lainnya seperti video editing akan berguna bagi disabilitas untuk menuju karir ke dunia kreatif fotografi. Dunia fotografi dan jurnalistik adalah dua hal yang saling terkait, penulisan menjadi keahlian yang dikuasai oleh penyandang disabilitas sebagai penulis. Kebutuhan akan adanya pelatihan jurnalistik bagi disabilitas menjadi penting sebagai titik awal disabilitas mengenali minat di bidang tersebut dan untuk selanjutnya dapat membangun karir di bidang tersebut.